Intraspecies typing of orthopoxviruses - Richardson, Madalene (Division of Medical Biochemistry and Structural Biology, 2017)
Characterization of viruses within the Orthopox genus has, in the past, been done by evaluating a spectrum of biological properties which gave different reactions in the different species. More recently analysis of genomic DNA by restriction endonucleases has proved a valuable additional way of identifying species and revealing intra-species variations among the orthopox viruses. This thesis reports the results of investigations of poxvirus isolates in which both biological characterization and DNA analysis have been used. Specimens of scabs from sick buffaloes in 18 outbreaks of buffalopox in India were extracted and virus was isolated from 13 of them by inoculation on chick embryo chorioallantoic membranes. The lesions resembled those of vaccinia and the isolates were confirmed as orthopox viruses by their susceptibility to neutralization by anti-vaccinial serum. Purified preparations of each isolate were made and the virion DNA extracted from them, was analysed by digestion with endonuclease Hind III, followed by electrophoresis to separate the resulting DNA fragments. The profiles of fragment sizes in the Hind III digest were indistinguishable from those of vaccinia isolates, but differed from other representative orthopoxviruses. This was the first examination of any DNA from the buffalopox virus. Six isolates were characterised in more detail. In biological tests, one of the six showed the ceiling temperature, rabbit virulence, cytopathic effect in cell monolayers and sensitivity to anti-vaccinial serum which is characteristic of vaccinia, and is regarded as an isolate of vaccinia. The other five had a lower ceiling temperature, were avirulent when inoculated in rabbits and were 10 - 50 fold less sensitive than vaccinia to neutralization with anti-vaccinia serum. In these properties they differed from vaccinia and resembled the buffalopox virus described by Baxby and Hill in 1971. Examination of virion DNA, using other restriction endonucleases showed that all five isolates could be grouped together and distinguished from a group of five vaccinia strains in digests with the endonuclease Sac I, Xho I and Eco RI. The sixth isolate which was biologically like vaccinia was also in the vaccinia group in these DNA analyses. Digestion of DNA obtained from all 12 of the non-vaccinia buffalo isolates showed the same profile and this profile differed from that of any of the vaccinia strains and also from the buffalopox isolate made 15 years previously in North India and described by Baxby and Hill. In another series of experiments the viral DNA from a number of isolates of monkeypox was analysed. One of these isolates was the first to be made from a wild caught animal (a squirrel) and the question was whether this isolate could be identified with isolates made from humans who had become infected in the same area of Zaire. All the isolates had previously been characterized biologically as being monkeypox virus. DNA was prepared from the squirrel isolate and from two human isolates from about the same time and district. No difference could be detected in the profiles of fragment sizes generated by digestion with the endonucleases Hind III or Pst I. To substantiate this apparent identity, DNA was prepared from another 9 monkeypox isolates from human infections with monkeypox in Liberia, Sierra Leone, Nigeria and Zaire as well as from five outbreaks in captive monkeys in Europe or America. The isolates covered the period from 1958 to 1986. The fragment size profiles established by electrophoresis of Pst I digests of all these DNA preparations were compared and found to fall into one of three distinct patterns. All the animal isolates from outside Africa had the same pattern as the isolates from Liberia and Sierra Leone. A second pattern was given by the two isolates from Nigeria and all the seven isolates from Zaire showed a third pattern. These observations supported the idea that the squirrel had been infected with the same variant of monkeypox virus that was causing the sporadic human infections in that country. The significance of the difference between the three patterns was investigated by constructing maps showing the location of Pst I cleavage sites on the genome of one isolate from each of the three main areas. A map had been published for Hind III cleavage sites on the genome of the Denmark strain of monkeypox virus. DNA from the Denmark strain was digested with Hind III, separated by electrophoresis in agarose gels and the fragments transferred by blotting onto nylon membranes. Fragments of DNA excised from gels after electrophoresis of Pst I digests were labelled by nick translation with 32 P-nucleotide and hybridized to the Hind III blots in order to determine the part of the genome from which each fragment came. By repetitions of this technique it was possible to construct Pst I maps of the genomes of representative strains of each of the three geographical variants of the virus. The sites which were different in the various isolates were found to be located in the centre and towards the left-hand end of the genome maps.